Anti-inflammatory effect of Cortex Eucommiae via modulation of the toll-like receptor 4 pathway in lipopolysaccharide-stimulated RAW 264.7 macrophages. (14th September 2017) - Koh, Wonil; Shin, Joon-Shik; Lee, Jinho; Lee, In-Hee; Lee, Sang Kook; Ha, In-Hyuk; Chung, Hwa-Jin
Abstract: Ethnopharmocological relevance: Cortex Eucommiae (CE), the bark of Eucommia ulmoides Oliv., has been traditionally used for its kidney-tonifying and bone- and tendon-enhancing properties in Korea, China, and Japan. CE has been historically prescribed for inflammatory conditions such as arthritis of the knee and ankle. Aim of the study: Although CE has recently been shown to suppress inflammation in scientific studies, whether this effect involves modulation of the toll-like receptor 4 (TLR-4) pathway is currently unknown. Materials and methods: The modulatory effect of CE on the TLR-4 pathway, both myeloid differentiation primary response gene 88 (Myd88)-dependent and independent, was investigated through real-time reverse transcriptase-polymerase chain reaction (RT-PCR), western blotting, and a reporter gene assay in lipopolysaccharide (LPS)-stimulated RAW 264.7 murine macrophages. Results: CE dose-dependently inhibited nitric oxide production without significant cytotoxicity with an IC50 of 356.23 μg/mL. In addition, CE down-regulated both LPS-induced mRNA and protein expression of inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), tumor necrosis factor-α (TNF-α), and interleukin-1β (IL-1β) in a dose-dependent manner. CE suppressed LPS-induced activation of nuclear factor-κB (NF-κB) and the mitogen-activated protein kinase (MAPK) pathways, which together comprise the Myd88-dependent TLR-4 pathway. The phosphoinositide 3-kinase (PI3K)/Akt/mammalian target of rapamycin (mTOR) pathway was also down-regulated by CE in a dose-dependent manner. CE additionally suppressed LPS-induced activation of interferon-β (IFN-β) and signal transducer and activator of transcription (STAT) pathway, which is associated with the Myd88-independent TLR-4 pathway. Conclusions: CE down-regulated both Myd88-dependent and independent TLR-4 pathways, thus exerting anti-inflammatory effects. These results suggest that CE may be used as a potential therapeutic agent against chronic inflammatory diseases. Graphical abstract: